Analyzing Customer Satisfaction: An Empirical Study on the Services Provided by Large Format Retail Stores in Tier-III Cities of India - Madhavedi, Sudhakar; Goh, Khang Wen; Choo, Wou Onn; Hoo, Wong Chee; Ling, Zhu (Journal of Ecohumanism, 2024)
Background: Large format retail stores, known as hypermarkets or superstores, have gained popularity in India. These stores offer diverse products and services, creating a convenient shopping experience. Despite success in urban settings, there is growing interest in expanding into rural areas. This paper explores whether these stores meet customer expectations and contribute to satisfaction in rural settings, assessing the suitability of this expansion perspective. Goal: India's retail focus has shifted to Tier-III cities and semi-urban towns due to market saturation in metropolitan areas. Customers in these regions expect higher service standards. This study evaluates customer satisfaction with services provided by large format retail stores in Tier-III cities and semi-urban towns. Design/Methodology/Approach: The study measures customer satisfaction derived from large format retail stores using the seven P’s of retail services marketing parameters. Data is collected from various Telangana districts through judgmental sampling, involving 100 customers through questionnaires and interviews. Analysis involves means, standard deviations, and weighted means, revealing moderate satisfaction with room for improvement. Findings/Results: Utilizing a five-point scale, the study identifies customer expectations and satisfaction across retailing service sub-parameters. Results show moderate satisfaction, suggesting opportunities for enhancing overall satisfaction, customer experience, and service quality.Originality: This study innovatively explores customer expectations from large format retail stores in Tier-III cities and semi-urban towns in India. It sheds light on customer satisfaction in the context of retail expansion into rural areas, emphasizing the need for strategic changes to meet customer expectations effectively. This paper offers a comprehensive exploration of the retail sector's role in sustainable development, covering economic, social, and environmental aspects. The findings and insights presented can guide retail operators and policymakers in fostering a more sustainable and inclusive retail environment in India.